Metode Penyimpanan Benih Merbau (Intsia bijuga O. Ktze) - Yuniarti, Naning (Institut Pertanian Bogor (IPB University), 2002)
This study describes a proper methode of seed storage to ensure merbau seeds remain viable after being separated from their host plant, and enable to germinate satisfactory by after planting. The aim of this research is to find out a proper methode of seed storage of merbau seeds. In implementing proper storage methode, three types of factors were tested, i.e : storage container (plastic, can, cloth bags, sack bags and bamboo box), storage room (air conditioned and room/ambient temperature); and storage durations (0, 2,4 and 6 months). The results showed that the most proper seed storage of merbau seeds was by using plastic bag container in an air conditioned room.